Types of Financing from Land Value Capture in Transit Oriented Areas in Terminal Baranangsiang - Hariyanto, Ario Bayu; Murtejo, Tedy; Alimuddin, Alimuddin (ASTONJADRO, 2023)
Transportation infrastructure plays an important role in increasing access and accelerating economic growth. The TOD design concept presents an area arrangement that is multi-use in nature and is integrated with the public transport network. Thus, there is another potential that can be captured from the high accessibility in the area, namely the opportunity to increase land value. The increase in land value comes as a result of the benefits obtained directly by residents of the TOD area, including various choices of transportation modes and also savings in transportation costs (Smith and Gihring, 2013). The method for capturing the increase in land value so that it is diverted for the development of facilities and infrastructure around the terminal or station location is known as Land Value Capture (LVC). The concept of Land Value Capture has been widely applied in many developing countries in the world. Among the many mechanisms and tools used in Land Value Capture, Jillella and Newman (2016) explain that joint development is the most widely used mechanism, followed by Tax Increment Financing and Property Tax. Thus in brief, TOD planning aims to increase accessibility in the area, where that accessibility can be converted into other sources of financing for the TOD project itself or the development of public transport infrastructure, through increasing land value with the LVC mechanism.